Synthesis and Structural Studies on MgO Nanoparticles Suitable for Tunnel Barrier Applications - S. Rizwan Ali; M. Naeem; S. Imran Ali; Sajida Azam; S. Naseem Shah; Zia-ur-Rehman; S. Masood Raza (Journal of Basic & Applied Sciences, 2015)
Magnesium oxide (MgO) nanoparticles are synthesized by a simple coprecipitation method. XRD studies reveal that nanoparticles are predominantly (100) textured with an average crystallite size of 19 nm.The relative peak intensities for (100) and (110) textured grains i.e., I(100)/I(110) is found to be ~ 2. Scanning electron microscope (SEM) pictures of our samples indicate that our synthesized nanoparticles are spherically shaped. Due to excellent electron tunneling features of (100) textured MgO nanoparticles, our synthesis method is suitable for cost effective and simple synthesis of pure MgO nanoparticles for applications involving electron tunneling.